Development of measles‑rubella surveillance health information system in the working area of health center tanjung selor, bulungan district - Andi C. Pertiwi; Ida Leida; Riwdan Amiruddin; Wahiduddin Wahiduddin; Suriah Suriah; Syamsuar Syamsuar (Journal of Public Health in Africa, 2023)
The Tanjung Selor Health Center reported 2 labora‑ tory‑confirmed negative measles suspected cases that occurred in the Tanjung Selor Hilir urban village area, thus meeting the Discarded Rate target of 80% for North Kalimantan Province. This study aims to design and determine the effectiveness of measles‑rubella surveillance applications based on increasing measles suspect case finding. This research used pre‑exper‑ imental study design and system development with the prototype method. This study was conducted in the working area of the Tanjung Selor Health Center. Samples of research were teachers and children of kindergarten/early childhood, elementary/boarding schools, and private pediatrician health service facilities in the Tanjung Selor Hilir village. The name of the application is SICARE (Sistem Campak Rubella/ Measles‑Rubella Surveillance) and expected to facilitate moni‑ toring reporting cases of measles rubella. Data were analyzed by univariate and bivariate t‑tests on Stata and then interpreted in the form of tables and narratives. The results showed the frequency of reporting (P=0.010), the difference in case of reporting before and after treatment (P=0.160), the effective‑ ness of surveillance attributes in schools and private facilities after treatment (P=0.00), and the effectiveness of reporting on Health Center officers (P=0.22). Significant results from the development of the SICARE application are the frequency of reporting and the effectiveness of surveillance attributes in schools and private facilities. It is recommended for health center staff to further develop the application that has been built through optimal planning to improve early detection and rapid response in an active measles‑rubella surveillance system.